Marx, Vygotsky and Freire: methodological discussions on the role of language in social transformation - Jones, Peter E; Magalhaes, Maria Cecilia C (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
This paper offers a Marxist grounding for a liberatory, criticalcollaboratory dialogic praxis in educational contexts and examines the implications of such praxis for an understanding of the potential role of the school as a site of critical thinking. Aligning with Stetsenko’s ‘Transformative-Activist Stance’, the discussion centres on clarifying the methodological rationale for approaching language as a means of cultural action and social transformation based on Marx’s materialist conception of history and the educationally based dialogical approaches of Vygotsky and Freire.